Differences in clinicopathologic variables between Borrelia C6 antigen seroreactive and Borrelia C6 seronegative glomerulopathy in dogs. (24th August 2019) - Borys, Moria A.; Kass, Philip H.; Mohr, Frederick C.; Sykes, Jane E.
Abstract: Background: Rapidly progressive glomerulonephritis has been described in dogs that seroreact to Borrelia burgdorfer i, but no studies have compared clinicopathologic differences in Lyme‐seroreactive dogs with protein‐losing nephropathy (PLN) versus dogs with Borrelia ‐seronegative PLN. Hypothesis/Objectives: Dogs with Borrelia C6 antigen‐seroreactive PLN have distinct clinicopathologic findings when compared to dogs with Borrelia seronegative PLN. Animals: Forty dogs with PLN and Borrelia C6 antigen seroreactivity and 78 C6‐seronegative temporally matched dogs with PLN. Methods: Retrospective prevalence case‐control study. Clinical information was retrieved from records of dogs examined at the University of California, Davis, Veterinary Medical Teaching Hospital. Histopathologic findings in renal tissue procured by biopsy or necropsy of dogs with PLN were reviewed. Results: Retrievers and retriever mixes were overrepresented in seroreactive dogs ( P  < .001). Seroreactive dogs were more likely to have thrombocytopenia ( P  < .001), azotemia ( P = .002), hyperphosphatemia ( P  < .001), anemia ( P  < .001), and neutrophilia ( P = .003). Hematuria, glucosuria, and pyuria despite negative urine culture were more likely in seroreactive dogs (all P  ≤ .002). Histopathologic findings were consistent with immune‐complex glomerulonephritis in 16 of 16 case dogs and 7 of 23 control dogs ( P = 006). Prevalence of polyarthritis was not different between groups ( P = .17). Conclusions and Clinical Importance: C6 seroreactivity in dogs with PLN is associated with a clinicopathologically distinct syndrome when compared with other types of PLN. Early recognition of this syndrome has the potential to improve outcomes through specific aggressive and early treatment.